The Role of Brand Image in Mediating the Influence of Social Media Marketing on Repeat Purchase of Kober Mie Denpasar Customers - Dinata, I Made Surya Yoga; Sukawati, Tjokorda Gde Raka; Suparna, Gede; Giantari, I Gst. Ayu Kt. (PT FORMOSA CENDEKIA GLOBAL, 2025)
Repeat purchase describes a customer’s decision to repurchase the same product or service, reflecting their satisfaction and that their expectations have been fulfilled. This research explores how brand image mediates the relationship between social media marketing and repeat purchase behavior among customers of Kober Mie Denpasar. A total of 130 respondents, selected through purposive sampling, completed a structured survey, and their responses were analyzed using SEM‑PLS 3. The analysis reveals that social media marketing has a direct, positive, and statistically significant impact on repeat purchase intentions. It also enhances brand image, which in turn positively influences the likelihood of customers making repeat purchases. Moreover, brand image functions as a crucial mediator, intensifying the effect of social media marketing on repeat buying behavior. These results underscore the importance for businesses to develop compelling social media strategies that not only generate immediate sales but also cultivate a strong brand image to support lasting customer loyalty.